Citizen Science for Bio-indication: Development of a Community-Based Index of Ecosystem Integrity for Assessing the Status of Afrotropical Riverine Ecosystems - Aura, Christopher Mulanda; Nyamweya, Chrisphine S.; Owiti, Horace; Odoli, Cyprian; Musa, Safina; Njiru, James M.; Nyakeya, Kobingi; Masese, Frank O. (Frontiers in Water, 2021)
The use of socioeconomic and cultural parameters in the assessment and biomonitoring of ecological health of aquatic ecosystems is still in its nascent stages. Yet, degradation of aquatic ecosystems has elicited concerns because of its bearing on social and economic development of communities consisting of marginalized and vulnerable groups, as well as the expenses and technical knowhow involved in biomonitoring approaches. In this study we developed a Citizen-based Index of Ecological Integrity (CIEI) for assessing and monitoring the ecological status of vulnerable African riverine ecosystems in Lake Victoria Basin, Kenya. The hypothesis is that the citizen-led socioeconomic and cultural metrics provides a more cost-effective broad view of ecosystems than other biomonitoring methods in the assessment of water resources in the developing countries. Selected rivers in the southern part of Lake Victoria (Rivers Kuja and Sondu-Mirui) recorded the highest CIEI than their northern counterparts (Rivers Yala and Nzoia) that had moderate to poor ecosystem integrities. The study demonstrates the usefulness of this approach to elucidate the source of impairment, the extent of impacts and provide a justifiable rationale to advice policy makers on developing guidelines for conservation and management of aquatic ecosystems. We recommend for adoption and promotion of the CIEI perspective in areas where such approaches appear defensible for the assessment of catchment-wide practices in areas with robust indigenous knowledge to provide a broad-view of the ecological health of the aquatic ecosystem.